Anxiety, depression, and stress: a comparative study between couples with male and female infertility - Zahra Bostani Khalesi; Fatemeh Jafarzadeh Kenarsari (BMC, 2024)
Abstract Background and aim Although infertility as a significant cause of marital crises is prevalent almost equally in men and women, infertile women are under more pressure and distress than infertile men. Therefore, this study was conducted aiming to compare anxiety, depression, and stress between couples with male and female infertility. Methods In this descriptive-analytical cross-sectional study, 40 couples (n = 80) with male infertility and 40 couples (n = 80) with female infertility were referred to the infertility clinic of Al-Zahra Educational and Medical Center, Rasht, Iran. Eligible infertile couples were selected by convenience sampling method. The data collection tool was a two-part questionnaire consisting of a demographic information form and a short form of the standard Depression Anxiety Stress Scale-21 (DASS-21). Data analysis was carried out using descriptive and inferential statistical tests at a significant level of p < 0.05. Results The severity of depression, anxiety, and stress also had a statistically significant difference between men and women. The severity of depression was mild in 57.5% of infertile women and moderate in 40% of infertile men. The severity of anxiety was moderate in 42.5% of infertile women and mild in 57.5% of infertile men. The severity of stress was Severe in 37.5% of infertile women and mild in 40% of infertile men. There was a statistically significant difference between infertile women and men in terms of depression (t=-4.213, df = 1619, p < 0.001), anxiety (t=-7.261, df = 2274, p < 0.001), and stress (t=-9.046, df = 2308, p < 0.001) subscales, and the total scores (t=-7.709, df = 2315, p < 0.001). The depression, stress and anxiety levels were higher in infertile women than in healthy women with infertile spouses. This difference was statistically significant (p < 0.01). The depression, anxiety, and stress levels were significantly different between infertile men and healthy men with infertile wives (p < 0.001). Conclusion The results of this study indicated that depression, anxiety, and stress were more prevalent in infertile women than in infertile men. The severity levels of depression, anxiety, and stress in the wives of infertile men were higher than those in the spouses of infertile women.